Designing optimal human‐modified landscapes for forest biodiversity conservation - Víctor Arroyo‐Rodríguez; Lenore Fahrig; Marcelo Tabarelli; James I. Watling; Lutz Tischendorf; Maíra Benchimol; Eliana Cazetta; Deborah Faria; Inara R. Leal; Felipe P. L. Melo; Jose C. Morante‐Filho; Bráulio A. Santos; et al. (Ecology Letters, 2020)
Agriculture and development transform forest ecosystems to human‐modified landscapes. Decades of research in ecology have generated myriad concepts for the appropriate management of these landscapes. Yet, these concepts are often contradictory and apply at different spatial scales, making the design of biodiversity‐friendly landscapes challenging. Here, we combine concepts with empirical support to design optimal landscape scenarios for forest‐dwelling species. The supported concepts indicate that appropriately sized landscapes should contain ≥ 40% forest cover, although higher percentages are likely needed in the tropics. Forest cover should be configured with c . 10% in a very large forest patch, and the remaining 30% in many evenly dispersed smaller patches and semi‐natural treed elements (e.g. vegetation corridors). Importantly, the patches should be embedded in a high‐quality matrix. The proposed landscape scenarios represent an optimal compromise between delivery of goods and services to humans and preserving most forest wildlife, and can therefore guide forest preservation and restoration strategies.